ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI DARI DAUN Eupatorium odoratum L. TERHADAP BAKTERI Staphylococcus aureus ATCC 25923 DAN Escherichia coli ATCC 25922 - Hasnawati Hasnawati; Erna Prawita (Majalah Obat Tradisional, 2010)
The leaves of Eupatorium odoratum L. have been used traditionally to cure abscess due to infectious diseases, leech bite and wound healing.  It was suspected that the leaves contain antibacterial compounds. The dried powder of E. odoratum leaves is extracted by Soxhlet using washbenzene and followed by methanol. Both extracts  are tested to determine their antibacterial activity by using diffusion test.  The active extract is fractionated by vacuum liquid chromatography. The active compound (2.3) obtained from the active fraction is purified by using preparative thin layer chromatography.  The UV-Vis spectrum of (2.3) (chloroform) showed λmax at 291nm. The IR spectrum of the active compound (2.3) (KBr) .0displayed signals (-OH), (-CHalifatik), (-CHalifatik), (-C=O), (C=C), (CH2), (CH3), (epoksi), and (C-O). 1H-NMR spectrum (CDCl3) showed signals at δ 1.26 ( 3H,s); 3.65 (3H,s); 3.82 (3H,s); 3.93 (3H,s); 4.53 (1H,d); 5.0 (1H,d); 5.7 (1H,d); 6.06 (1H,d); 6.14 (1H,d); 6.93 (1H,d); 7.05 (1H,dd); dan 7.16 (1H,d) ppm. This spectrum is suspected to be an epoxide chalcone type of compound. The active  compound (2.3) at minimum loading of 250 µg showed bacterial growth inhibition on S. aureus and E. coli at diameter 9.5 and 7.2 mm respectively.